Cretaceous-Cenozoic history of the southern Tan-Lu fault zone: apatite fission-track and structural constraints from the Dabie Shan (eastern China) - Grimmer, Jens Carsten; Jonckheere, R.; Enkelmann, E.; Ratschbacher, L.; Hacker, B. R.; Blythe, A. E.; Wagner, Günther A.; Wu, Q.; Liu, S.; Dong, S. (Tectonophysics, 2002)
Apatite fission-track (AFT) and structural data outline the Late Cretaceous−Cenozoic history of the southern Tan-Lu fault zone (TLFZ), one of Asia's major faults, the Triassic-Jurassic Dabie orogen, Earth's largest track of ultrahigh-pressure rock exposure, and its foreland, the Yangtze foreland fold-thrust belt. The fission-track analyses utilized the independent (φ-), Z- and ξ-methods for age determination, which yielded within error identical ages. Ages from Triassic-Jurassic syn-orogenic foreland sediments are younger than their depositional age and thus were reset. A group of ages records rapid cooling following shallow emplacement of granitoids of the widespread latest Jurassic−Early Cretaceous “Yanshanian” magmatism. Most ages are 90 to 55 Ma and document cooling following reheating at 110-90 Ma, the time when the basement units of the Dabie Shan were last at >200 °C. This cooling coincides with rifting marked by the Late Cretaceous−Eocene red-bed deposition in eastern China. During this period, the Dabie basements units exhumed in the footwall of the Tan-Lu fault with the Qianshan basin in the hanging wall; the associated stress field is transtensional (NW-trending principal extension direction). The youngest fission-track ages and temperature-time path modeling point to enhanced cooling in the footwall of the Tan-Lu and associated faults at 45±10 Ma. The related stress field is transtensional, with the principal extension direction changing trend from NW to W. It may be the far-field expression of the India-Asia collision superposed on the back-arc extension setting in eastern China. A regional unconformity at ∼25 Ma marks an upper bound for the inversion of the Late Cretaceous−Eocene rift structures. During the Neogene, further subsidence in the eastern China basins was accommodated by sub-horizontal NE-SW extension, and followed by the presently active NW-SE extension. The Tan-Lu fault along the eastern edge of the Dabie Shan had normal and then sinistral-transpressive motion during the Late Cretaceous−Eocene. Its motion changed during the Neogene from sinistral transtensive to normal and then to its present dextral transtensive activity.
Gesehen am 23.09.2020